PENGARUH PENGGUNAAN INSTAGRAM MARKETING TERHADAP BRAND AWARENESS UMKM ONELAUNDRY DI YOGYAKARTA - Rosana, Yuliana; Wahyono, Teguh (POLITEKNIK LP3I JAKARTA, 2026)
This research is motivated by the increasing use of social media as a digital marketing tool by UMKM. This study aims to analyze the influence of Instagram marketing on consumer brand awareness at Onelaundry UMKM in Yogyakarta and identify the most dominant influencing factors. This study used a quantitative approach with descriptive and verification methods. The study population was consumers familiar with Onelaundry services in Yogyakarta, with a sample of 50 respondents selected using a purposive sampling technique. Data collection was conducted through an online questionnaire, while data analysis used validity and reliability tests, classical assumption tests, and multiple linear regression with the help of SPSS. The results showed that Instagram marketing had a significant effect on brand awareness with a coefficient of determination of 87.8%. Visual design was the most dominant factor influencing brand awareness, followed by Instagram advertising. This study recommends that UMKM focus their marketing strategies more on strengthening visual design and utilizing Instagram Ads to increase brand awareness.